Extending advice response theory to the advisor: Similarities, differences, and partner-effects in advisor and recipient advice evaluations. Issue 1 (2nd January 2020) - Guntzviller, Lisa M.; Liao, Danni; Pulido, Manuel D.; Butkowski, Chelsea P.; Campbell, Aaron D.
ABSTRACT: We extended advice response theory by drawing from construal-level theory to understand advisors' evaluation processes and how advisors' and recipients' evaluations impact each other. An actor-partner interdependence model ( N  = 130 dyads) indicated, for both advisors and recipients, advisor expertise assessments were positively associated with advice facework and efficacy evaluations, which were positively associated with advice quality ratings. Advisors rated certain aspects of their advice more favorably than recipients, viewed absence of limitations as more important when rating advice quality, and were less influenced by their relational satisfaction when evaluating message features. We examined how recipient-to-advisor and advisor-to-recipient significant effects manifested in conversations using post-hoc qualitative analyses and found that behaviors are role-dependent and may reflect role-specific construal levels.